Sosial Media Sebagai Strategi Untuk Meningkatkan Branding Kelompok Tani Maju 01 - Taufik Rizal Dwi Adi Nugroho; Aulia Kafi Yugi Shah; Era Vanessa Noer (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The Farmer Group